A Practitioner's Guide to End-of-Life Intimacy: Suggestions for Conceptualization and Intervention in Palliative Care. (May 2018) - Morrissey Stahl, Kate A.; Bower, Kyle L.; Seponski, Desiree M.; Lewis, Denise C.; Farnham, Andrea L.; Cava-Tadik, Yasemin
Sexuality and intimacy, including contact, tenderness, and love, are important at every life stage. Intimate expression is especially vital at the end of life, when relationships with loved ones are time limited. Unfortunately, care providers often ignore the potential need for sexual expression, especially at the end of life. In this article, we consider current research on sexuality and end-of-life care and situate these two fields in an ecological framework. We explore how end-of-life sexuality and intimacy can be supported by practitioners in multiple nested contexts and provide suggestions for theoretically-driven interventions. We also provide reflexive considerations for practitioners.